2019
DOI: 10.1021/acs.est.8b06122
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning and Bioaccumulation of Legacy and Emerging Hydrophobic Organic Chemicals in Mangrove Ecosystems

Abstract: Knowledge regarding partitioning behavior and bioaccumulation potential of environmental contaminants is important for ecological and human health risk assessment. While a range of models are available to describe bioaccumulation potential of hydrophobic organic chemicals (HOCs) in temperate aquatic food webs, their applicability to tropical systems still needs to be validated. The present study involved field investigations to assess the occurrence, partitioning, and bioaccumulation behavior of several legacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…The presence of a stable transformation product of HHCB, HHCB-lactone, has been reported in biota (Lange et al, 2015;Trabalón et al, 2015), but its use as a tracer for metabolism warrants further research as it can also originate in the environment by chemical, photochemical and/or microbiological processes. In marine bivalves, similar bioaccumulation factors for HHCB and AHTN have been reported for Lokan clams (Polymesoda expansa) and Asian green mussels (Perna viridis) (Bayen et al, 2019). HHCB and AHTN were also found to correlate regardless of the species (Perna viridis, Mytilus edulis.)…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 74%
See 1 more Smart Citation
“…The presence of a stable transformation product of HHCB, HHCB-lactone, has been reported in biota (Lange et al, 2015;Trabalón et al, 2015), but its use as a tracer for metabolism warrants further research as it can also originate in the environment by chemical, photochemical and/or microbiological processes. In marine bivalves, similar bioaccumulation factors for HHCB and AHTN have been reported for Lokan clams (Polymesoda expansa) and Asian green mussels (Perna viridis) (Bayen et al, 2019). HHCB and AHTN were also found to correlate regardless of the species (Perna viridis, Mytilus edulis.)…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 74%
“…There is a general agreement on the finding of ratios close to 1 in air and background sites primarily under influence of atmospheric depositions, where AHTN is more stable to atmospheric oxidation processes (Lange et al, 2015;McDonough et al, 2016;Xie et al, 2007). When comparing sediments and water, some authors have reported ratios closer to 1 in sediments, primarily due to a stronger tendency of AHTN for sorption and/or a degradation of HHCB into its lactone derivative in sediment (Bayen et al, 2019;Heberer, 2002;Lu et al, 2015).…”
Section: Hhcb / Ahtn Diagnostic Ratiomentioning
confidence: 53%
“…The influence of matrix complexity (organic matter) on dissolved HOC concentrations was investigated in lab exposures [174]. PSDs were deployed in coastal waters and used to predict the concentrations of HOCs in other environmental compartments through equilibrium models [175,176]. PSDs have been exposed in sediments, pore waters, waters and the overlying atmosphere (gaseous and aerosol) to determine activity gradients across environmental compartments [177][178][179][180][181][182][183][184][185].…”
Section: Chemical Speciation Distribution and Degradationmentioning
confidence: 99%
“…7 Therefore, it follows that biodiversity loss and ecosystem services are closely related, and have the potential to affect both human health and global economies. 10 Because the spread of chemical pollutants in the environment represents a serious concern for ecosystem health 11 , holistic approaches such as One Health and Eco-Health have emerged in the last few years. Both these approaches assume that humans, animals, and the ecosystems to which they belong interact in a complex way and at different levels.…”
Section: Introductionmentioning
confidence: 99%
“…Such activities involve the release of ubiquitous environmental chemical pollutants such as organochlorine compounds (OCs) and heavy metals. 11,19 It follows that chemical pollution is a global emergency concerning the health of all the different ecosystem components, i.e. environment, animals, humans.…”
Section: Introductionmentioning
confidence: 99%